Trends in the Design of Technical Products from the perspective of TTS - Josef DVORAK; Stanislav HOSNEDL (Communications of International Proceedings, 2022)
Technical Products are constantly being innovated. This fact can be observed in the development and transformation of almost all Technical Products (TS). In some areas of Technical Product development, there is minimization, automation, digitization or even the involvement of artificial intelligence in the actual design of Technical Products. Engineering Design Science and methodology (EDSM) espacially Theory of Technical Systems (TTS) was used for investigation and determination of which constituents of Technical Products are used in design trends more often then others. In future steps the segment of Technical Products for determintion will be choosen and conclusion will be stated.
Keywords: Technical Product; heterogenous system; constituents; trends; design